Competitive Strategy Analysis to Increase Consumer Purchasing Decisions on Minimarket Business - Agus Supandi Soegoto; Herman Karamoy (Faculty of Economic and Business, 2020)
The growth of the minimarket business in Indonesia is high-speed and exciting. As a result, the competition is very tight. This study aims to analyze the effect of product quality, price discounts, and servicescape on a consumer purchasing decision. This research uses associative descriptive methods and multiple linear regression analysis techniques. The research sample is to minimarket consumers in the cities of Manado, Tomohon, and Bitung. These results indicate that for consumers, the three variables are the main elements considered when shopping at the minimarket. The right management strategy will improve consumers' decision to buy products, thereby increasing profits and maintaining business sustainability. Management should always have attention to product quality by combining the right price discounts and servicescape to increase purchases, high profits, and superiority in competition.JEL Classification: M21, M31How to Cite:Soegoto, A. S., & Karamoy, H. (2020). Competitive Strategy Analysis to Increase Consumer Purchasing Decisions on Minimarket Business. Etikonomi: Jurnal Ekonomi, 19(1), 119 – 130. https://doi.org/10.15408/etk.v19i1.14337.